2020
DOI: 10.3390/genes11091108
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Revealed an Emerging Role of Alternative Splicing in Embryonal Tumor with Multilayered Rosettes

Abstract: Embryonal tumor with multilayered rosettes (ETMR) is an aggressive and rare pediatric embryonal brain tumor. Amplification of C19MC microRNA cluster and expression of LIN28 are distinctive features of ETMR. Despite the increasing efforts to decipher ETMR, the biology remains poorly understood. To date, the role of aberrant alternative splicing in ETMR has not been thoroughly investigated. In the current study, a comprehensive analysis was performed on published unprocessed RNA-seq reads of tissue-matched ETMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In engineering practice, the pile-soil relationship is often complex. Many studies and experiments [20,21] have revealed that when pile spacing is small enough, a soil arching effect will occur between soil and piles, making it possible for piles to do more negative work on the soil.…”
Section: Plos Onementioning
confidence: 99%
“…In engineering practice, the pile-soil relationship is often complex. Many studies and experiments [20,21] have revealed that when pile spacing is small enough, a soil arching effect will occur between soil and piles, making it possible for piles to do more negative work on the soil.…”
Section: Plos Onementioning
confidence: 99%